(untitled) (International Journal of Food and Nutritional Sciences, 2021)
This study delves into a crucial juncture in the larger discourse on LGBTQIA+ rights in India, specifically focusing on the experiences of transgenders. It aims to comprehend the impact of social beliefs and representations on transgender identities and their access to services. Through an exploration of complex cultural and literary discourses, the study highlights the intricate dynamics involved in the negotiation of transgender identities within the broader social system. Drawing from extensive analyses of scholarly literature, historical documents, and literary works, the study investigates how literary and cultural narratives reflect and reinforce societal attitudes towards transgender people, influencing their experiences of marginalization and isolation. By doing so, the research expands our understanding of the challenges faced by transgender individuals in India and provides perspectives for the promotion of inclusive and equitable welfare programs.